Psychometric Evidence of Factorial Structure of Ambivalent Sexism in Brazilian Psychologists - Gaspodini, Icaro Bonamigo (2019)
A perspective to assess prejudice against women can be obtained through the Ambivalent Sexism Inventory (ASI). Ambivalent sexism consists of two forms of manifestation: hostile and benevolent. The main objective of this study was to evaluate the factorial structure of ambivalent sexism in a sample of Brazilian psychologists. In addition, ambivalent sexism was also evaluated in relation to age, time served and how much the professional identified with a list of psychology fields. A total of 497 psychologists, between the ages of 22 and 69 (M = 34.52; SD = 9.57) from all regions of the country responded to an online survey. In addition to descriptive statistical analysis, the confirmatory factor analysis was carried out using several quality indices to adjust the model to the data, and the associations were calculated with Pearson’s correlations. Results showed reliable psychometric scores for the bifactorial structure of ambivalent sexism (hostile and benevolent). Sexism was positively correlated with age and showed no correlations with time of occupation. As far as the identification with psychology fields, sexism was negatively correlated with Social and Community Psychology, and positively correlated with Psychological Evaluation, Neuropsychology and Behavioral Neurosciences, Sport Psychology, Traffic Psychology, Experimental Psychology and Organizational Psychology.